Knowledge-based design support and discourse management in user interface management systems - Löwgren, Jonas (Linköping studies in science and technology. Dissertations ;, 1991)
Abstract: "This dissertation is about User Interface Management Systems (UIMSs), and more specifically about new ways to extend the scope and the functionality of these systems. I define a UIMS as an interactive tool or set of tools intended to facilitate the design, development and delivery of user interfaces. The assumption underlying the application of UIMS techniques to software development is that the user interface can to some extent be separated from the underlying functionality of the application. Current UIMS technology is, however, not capable of coping with this separation in the case of conversational expert systems.